2015
DOI: 10.3168/jds.2014-8791
|View full text |Cite
|
Sign up to set email alerts
|

Effects of slow-release urea and rumen-protected methionine and histidine on performance of dairy cows

Abstract: This experiment was conducted with the objective to investigate the effects of slow-release urea and rumen-protected (RP) Met and His supplementation of a metabolizable protein (MP)-deficient diet (according to NRC, 2001) on lactation performance of dairy cows. Sixty lactating Holstein cows were used in a 10-wk randomized complete block-design trial. Cows were fed a covariate diet for 2 wk and then assigned to one of the following treatments for an 8-wk experimental period: (1) MP-adequate diet [AMP; 107% of M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

28
91
9

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 80 publications
(128 citation statements)
references
References 78 publications
28
91
9
Order By: Relevance
“…The greater concentrations of His, Leu, and Val with ESBM in the current experiment can be explained with increased supply of these AA with RUP, compared with SSBM. Carnosine is a dipeptide containing β-Ala and His and muscle carnosine is considered an endogenous source of His in ruminants or monogastric animals (see discussion in Giallongo et al, 2015). Its increased concentration with the ESBM diets is in agreement with the increased plasma His concentrations.…”
mentioning
confidence: 78%
“…The greater concentrations of His, Leu, and Val with ESBM in the current experiment can be explained with increased supply of these AA with RUP, compared with SSBM. Carnosine is a dipeptide containing β-Ala and His and muscle carnosine is considered an endogenous source of His in ruminants or monogastric animals (see discussion in Giallongo et al, 2015). Its increased concentration with the ESBM diets is in agreement with the increased plasma His concentrations.…”
mentioning
confidence: 78%
“…The experimental procedures were in accordance with the guidelines of the Animal Care and Use Committee at The Pennsylvania State University. Cows, experimental design, and treatments were described in detail by Giallongo et al (2015). Briefly, the trial was conducted in 2 phases each consisting of 30 lactating Holstein cows.…”
Section: Animals Treatments and Experimental Designmentioning
confidence: 99%
“…Feeding a nutrient-restricted diet (68.1% of NE M and 86.7% of MP requirements) to Angus-Gelbvieh crossbred cows was associated with a downregulation of mTOR signaling and a higher amount of ubiquitinated proteins, suggesting a decrease in protein synthesis and enhanced protein degradation in muscle (Du et al, 2005). In the main experiment of this study (Giallongo et al, 2015), feeding a 5% MPdeficient diet based on the NRC (2001) requirements did not decrease DMI and yields of milk and milk components; however, it increased or tended to increase plasma concentrations of 3-methylhistidine (3-MH; an indicator of myofibrillar protein breakdown) when compared with an MP-adequate diet and an MP-deficient diet supplemented with slow-release urea, respectively. In addition, the results from the main experiment demonstrated that cows receiving the MP-deficient diet had less BW gain than those fed MP-adequate diet or slowrelease urea and RPAA-supplemented diets (Giallongo et al, 2015).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…The DMI and milk production were decreased when feeding of metabolizable protein deficient diets (Lee et al, 2011;2012a). On the contrary, when DMI did not decrease, milk production was also not different from diets with adequate metabolizable protein (Lee et al, 2012b;Giallongo et al, 2015).…”
Section: Feed Intake and Milk Yieldmentioning
confidence: 91%